Improving Junior High School Students' Learning Outcomes on State Changes of Matter Through Experimental Teaching Methods - Anastasia Depa; Yulita Adelfin Lede; Geterudis Kerans (CV. Dharma Samakta Edukhatulistiwa, 2026)
Student learning outcomes in science subjects often experience problems such as low learning outcomes due to the application of conventional learning models. This makes students passive and learning boring and non-contextual. To overcome this problem, one model that can be used is the experimental model, which is expected to improve student learning outcomes by actively involving them in the learning process directly. The purpose of this study was to determine the effect of the experimental method on student learning outcomes on the material on changes in the state of matter in class VII of junior high school. The type of research used was quasi-experimental research with a pretest-posttest control group design. There were 27 students in the study, with 14 students in the experimental class and 13 students in the control class. The research instrument was a multiple-choice test consisting of 20 questions that had been tested for validity and reliability. Data collection techniques were carried out through pretest and posttest, while data analysis used the Mann-Whitney U Test non-parametric test with the help of SPSS version 16.0. The results showed a significant difference in learning outcomes between the experimental class and the control class with a significance value of 0.000 < 0.05. This proves that the application of the experimental method has an effect on student learning outcomes in class VII on the material on changes in the state of matter.